2021
DOI: 10.1088/1402-4896/ac14e2
|View full text |Cite
|
Sign up to set email alerts
|

Surface effect on vibration characteristics of bi-directional functionally graded nanobeam using Eringen’s nonlocal theory

Abstract: A nonlocal model capturing the surface and size effects has been proposed to investigate the vibration behavior of bi-directional functionally graded nanobeam. The material properties of nanobeam are assumed to vary as per the power-law distribution in both the thickness and length directions. For the analysis, surface and size effects have been incorporated by employing the Gurtin-Murdoch surface theory and Eringen's nonlocal theory, respectively. Using Hamilton's principle, the governing equation of motion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Since researchers have adopted this theory, numerous investigations have widely confirmed its effectiveness in computing the induced behavioral shift due to the effect of small sizes for components with nanometric dimensions [33]. Presently, analyses have applied the nonlocal approach to various types of materials [34,35] to determine both linear [36] and nonlinear [33] vibrations for uniform or nonuniform [37,38] cross-sections. Ghorbanpour Arani et al [39] concluded that the shift in local behavior with respect to nonlocal behavior increases according to a parametric function in relation to the wave number.…”
Section: Introductionmentioning
confidence: 99%
“…Since researchers have adopted this theory, numerous investigations have widely confirmed its effectiveness in computing the induced behavioral shift due to the effect of small sizes for components with nanometric dimensions [33]. Presently, analyses have applied the nonlocal approach to various types of materials [34,35] to determine both linear [36] and nonlinear [33] vibrations for uniform or nonuniform [37,38] cross-sections. Ghorbanpour Arani et al [39] concluded that the shift in local behavior with respect to nonlocal behavior increases according to a parametric function in relation to the wave number.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, FG materials have been employed extensively as the face sheets of sandwich structures since their great strength and toughness allow them to tolerate significant mechanical and thermal loads while still maintaining a long operating life, a quality that is not present in other materials. These materials can be created in two ways: one is to add nanofillers in the thickness direction of a structure through FG patterns, and the other way is to utilize an FG function to relate two different materials (typically metal and ceramic) to each other in the top and bottom surfaces of a structure [11][12][13]. In this regard, some analytical research concerning the static and dynamic behavior of sandwich structures containing FG metal-ceramic layers will be surveyed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Jalaei et al [74] contributed to the field by investigating the linear dynamic instability of simplysupported FG nanobeams under axial excitation load applying nonlocal strain gradient theory. In another investigation, Dangi and Lal [75] analyzed the vibrational response of the bi-directional FG nanobeams by using the differential quadrature method. Furthermore, in the scope of the plate structures, the effect of spatial variation of the nonlocal parameter on the vibrational behavior of the graded sandwich rectangular nanoplates was reported in the research of Van Vinh and Tounsi [76] employing the modified nonlocal theory.…”
Section: Introductionmentioning
confidence: 99%